Manajemen Kurikulum Integratif Madrasah dan Pesantren di Era Kurikulum 2013 - Mohammad Saefullah (Andragogia: Journal Education Science And Islamic Studies, 2025)
This study aims to describe the planning, implementation, and evaluation of the integrative curriculum management between madrasahs and Islamic boarding schools (pesantren) in MTs NU Patrol Indramayu and Asy-Syarifiyyah Sunan Gunung Jati Islamic Boarding School. The study was motivated by the moral degradation among students and the importance of integrating religious values into the formal curriculum. A qualitative approach with a multisite case study method was employed. Data collection techniques included observation, in-depth interviews, and documentation. The findings reveal that curriculum planning integrates curriculum objectives and content; implementation aligns program execution and supervision; and evaluation is conducted coordinatively using context, input, process, and product evaluation models. This study concludes that integrative curriculum management can serve as a strategic solution for holistic character education